DAMPAK BAHAYA MAKANAN GORENGAN BAGI JANTUNG - Yuspa Hanum (JURNAL KELUARGA SEHAT SEJAHTERA, 2016)
Fried containing many lipids and cholesterol, often leads to diseases , as the heart . Consume fried neat sold at the sidewalks and many places in the country are very risky. Food fried generally cooked with cooking oil the results of repetition in high temperature and for a long time (deep frying). This kind of food that contributes to intake highest trans fatty acid. Fatty acids kind of this became one of the causes of the increasing disease resulting from obstruction of the blood vessels, one of them is heart disease. For human healthy, Recommended intake of trans fatty less than 1 % calories daily needs. If you need calories 2000 calories a day, Then trans fatty intake must not over 20 calories a day or similar to 2 trans fatty grams a day. If consumed in quantity high trans fat can improve the low density lipoprotein (LD) and can lower the levels good cholesterol High Density Lipoprotein (HDL). If trans fat consumed daily 1-3 % course can already raises the risk of a heart attack for adults.Kata kunci : Minyak goreng, Gorengan, Jantung